10× faster synthesis of chalcogenide solid solutions with tunable S : Se ratio by NaBH4-activated S + Se precursors. Issue 109 (11th November 2016) - Zhang, Xiaokun; Bai, Yuling; Liu, Wen; Sun, He; Peng, Xiaoli; Xiang, Yong; Zhang, Shu
Abstract : A 10× faster solvothermal method to synthesize metal chalcogenide solid solutions with tunable S : Se ratio by activated multi chalcogen precursors. Abstract : Reducing the reaction time of solvothermal synthesis has significance not just for industrial but for academic applications. In this paper, we develop a 10× faster solvothermal method to synthesize metal chalcogenide solid solutions with tunable S : Se ratio by activated multi chalcogen precursors.